The development of small town waterfronts - Lorg, John L. (Kansas State University, 2006)
This study focuses on the waterfront redevelopment process associated with small town redevelopment projects. The goal of this study will be to identify common and/or unique factors limiting and/or creating opportunities in the creation of small scale waterfronts. Many waterfronts of today have evolved from the unfriendly working waterfronts of the past, to a post-industrial environment sensitive to users needs. With the inception of these user friendly waterfronts, many communities have experienced positive results influencing economics, community image, increased socialization in addition to many other positive attributes. Unfortunately, smaller communities looking to take advantage of these desirable features often lack the resources needed to incorporate a waterfront redevelopment. Many professionals involved in these unique projects are often challenged by the constraints associated with small scale riverfronts. The goal of this research topic will be to gain a better understanding, from a professional perspective, what issues challenge the redevelopment process and why these challenges often curtail small scale waterfront projects. In an effort to better understand waterfront redevelopment, research involved background studies highlighting historical aspects, design, and implementation. In addition to background studies, case studies of the successful Owensboro and Atchison Riverfront projects were developed enabling the identification of key factors essential to small scale redevelopment. Furthermore, an annotated outline was developed as a guide for future communities to utilize as a foundation necessary in the successful implementation of a small scale waterfront redevelopment.
Keywords: Waterfront; Riverfront; Small town; Landscape Architecture (0390)